2012
DOI: 10.3402/meo.v17i0.17172
|View full text |Cite
|
Sign up to set email alerts
|

Are medical students accepted by patients in teaching Hospitals?

Abstract: BackgroundWorldwide, patients are the cornerstone of bedside teaching of medical students. In this study, the authors aimed to assess patients’ acceptability toward medical students in teaching hospitals of the Faculty of Medicine of Kuwait University.MethodsNinehundred and ninety five patients were approached in 14 teaching hospitals; 932 patients agreed to participate (refusal rate is 6.3%). A self-administered questionnaire was used to collect data.ResultsIn general, higher acceptance of students by patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 15 publications
9
75
3
2
Order By: Relevance
“…[23] For example, patients’ comfort level towards involving medical students in performing less invasive examination and minor procedures was consistently high across different specialties in the US;[45] however, in Kuwait[6] and Ethiopia,[7] more than half the patients refused that kind of involvement.…”
Section: Introductionmentioning
confidence: 99%
“…[23] For example, patients’ comfort level towards involving medical students in performing less invasive examination and minor procedures was consistently high across different specialties in the US;[45] however, in Kuwait[6] and Ethiopia,[7] more than half the patients refused that kind of involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Encounters with patients can promote contextual and clinical learning, improve communication and professional skills and initiate the development of a future doctor-patient relationship. Patients' willingness to cooperate and contribute to the education and training of medical students provide better teaching opportunities for students at most levels of patient care (Marwan et al 2012). Medical education researchers suggested that bedside teaching is affected by four factors: teaching curriculum, clinical supervisors, medical students and patients (Sayed-Hassan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Patients are active participants in choosing their care, leading to difficulty in training students if patients decline their involvement. With increased focus on patients' rights and informed consent, patients can now choose whether to have medical students present during their consultations (Marwan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Öte yandan tüm hastaların %39'u tıp öğrencileri tarafından sorgulanmayı ve muayene olmayı doktorun gözetiminde de olsa istememiştir. Bu durumun en olası nedeni öğrencilerin tıbbi beceri ve yaklaşımlarına güvensizlik olabilir 15 . Bunun yanında hastalar özel durumlarını doktorları dışında biriyle paylaşmak istemiyor da olabilir.…”
Section: Discussionunclassified